NIEWYDOLNOŚĆ SERCA I PŁUC, TRANSPLANTOLOGIAInfluence of selected donor characteristics on the troponin I levels after heart transplantation: a single centre experience - Wierzbicki, Karol; Sobczyk, Dorota; Milaniak, Irena; Bochenek, Maciej; Kapelak, Bogusław; Drwiła, Rafał; Wróbel, Krzysztof; Bartuś, Krzysztof; Ciołczyk-Wierzbicka, Dorota; Przybyłowski, Piotr; Sadowski, Jerzy (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2011)
Introduction: The selected factors connected with the heart donor may influence the extent of the harvested heart injury. Aim of the study : To assess the influence of selected factors connected with heart donor on troponin I levels in the perioperative period (from day 0 to day 3). Material and methods : Retrospective analysis included 30 patients (4 females, 26 males) aged 22 to 62 years, average 48.5 ±11.00. The study group consisted of the patients whose hearts were harvested according to the same scheme. In all patients, troponin I levels were measured on the consecutive days after HTX. The following features were analyzed: donor’s age, cause of donor’s death, vasopressants’ use and total ischemic time (TIT). Troponin I levels were measured by one step immunoenzymatic test (normal values up to 0.1 ng/ml). Results : A inverse significant correlation between TIT (mean 218.8 min ±44.2) and troponin I levels in the period between day 0 and two days after HTX was observed. No influence of vasopressants on troponin I levels was noted. The weak trend towards (r = 0.3; p = 0.17) the positive correlation between donor’s age and troponin I levels on the 1st day after HTX was observed. Similarly, the weak trend towards the positive correlation between stroke and higher troponin I levels on the 1st postoperative day (p = 0.16) was observed. Conclusion: TIT does not correlate positively with increased troponin I values. The relationship demands further analysis. The donor’s age and stroke as the cause of the donor’s death can potentially influence higher troponin I levels (no statistical significance).